PERANAN KEBIJAKAN PUBLIK, ORIENTASI KEWIRAUSAHAAN DAN KOMPETENSI SUMBERDAYA MANUSIA DALAM PENGEMBANGAN PRODUK PERIKANAN PRIMA - Abdul Rokhman; John Haluan; Ari Purbayanto; Victor P.H. Nikijuluw (Buletin PSP, 2007)
Development of fish processing industry in Indonesia obtain a new momentum since issuing the act No. 31/2004 regarding fisheries and determining of agriculture revitalization in the National Development Agenda 2004-2009. The strategy that can be carried out to accelerate development of fish processing industry is development of Prime Fishery Products, those are high quality, safety, competitive and high value added fishery products. The aim of research is to improve quality of public policies in development of fish processing industry, by analyzing factors those have role to Prime Fishery Products, which are (1) public policy related to quality and safety assurance, (2) entrepreneurial orientation, and (3) human resource competency. The research sample is frozen fish processing plants located in Banten Province, Jakarta Province, West Java Province, Central Java Province, Yogyakarta Province and East Java Province. The research is used the descriptive method survey and compiled data are analyzed using Structural Equation Modeling (SEM) method. The result of research is point out criteria of Prime Fishery Products that strongly influence is competitiveness, followed by quality and safety assurance. While value adding is not significantly influence. All determinant factors of Prime Fishery Products are significantly having roles. The leading role is entrepreneurial orientation, followed by public policy and human resource competency.